2014
DOI: 10.1038/cddis.2013.553
|View full text |Cite
|
Sign up to set email alerts
|

miR-1207-5p and miR-1266 suppress gastric cancer growth and invasion by targeting telomerase reverse transcriptase

Abstract: hTERT is the catalytic subunit of the telomerase complex. Elevated expression of hTERT is associated with the expansion and metastasis of gastric tumor. In this study, we aimed to identify novel tumor suppressor miRNAs that restrain hTERT expression. We began our screen for hTERT-targeting miRNAs with a miRNA microarray. miRNA candidates were further filtered by bioinformatic analysis, general expression pattern in different cell lines, gain-of-function effects on hTERT protein and the potential of these effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 41 publications
2
76
0
Order By: Relevance
“…Although altered expression of several miRNAs has been involved in the regulation of hTERT [1215], the epigenetic mechanisms that caused elevated hTERT expression in OC remain poorly characterized. In this study, we have attempted to identify tumor suppressor miRNAs that modulate hTERT expression in OC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although altered expression of several miRNAs has been involved in the regulation of hTERT [1215], the epigenetic mechanisms that caused elevated hTERT expression in OC remain poorly characterized. In this study, we have attempted to identify tumor suppressor miRNAs that modulate hTERT expression in OC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of hTERT was induced with a HIV-based lentiviral vector system, as previously described 11. The packaged lentiviruses were referred as lenti-hTERT and lenti-Control.…”
Section: Methodsmentioning
confidence: 99%
“…Chen L et al showed that miR- 1207 suppresses gastric cancer growth and invasion by targeting telomerase reverse transcriptase (hTRET) [2]. MiR-1207-5p was significantly upregulated in gastric cancer patients without lymph node metastasis (LNM) compared with those with LNM [3].…”
Section: Introductionmentioning
confidence: 99%